Penguatan Kewirausahaan Mahasiswa KKN Institut Ahmad Dahlan Melalui Produksi Kerupuk Nuris di Triwung Kidul - Danis Chusniyah; Ahmad Qhusyaery; Reza Hilmy Luayyin (Lembaga Penelitian, Penerbitan, dan Pengabdian Masyarakat, 2024)
The Ahmad Dahlan Institute's Community Service Program (KKN) with the theme “Optimizing the Potential of MSMEs with Innovations Based on Local Wisdom” not only functions as a community service activity, but also a medium for strengthening students' entrepreneurial skills. This study aims to identify and analyze the strengthening of KKN students' entrepreneurship through the production of Nuris crackers in Triwung Kidul. Nuris cracker production was chosen as a form of local economic empowerment that involves students in the entire process, from production to marketing. The research method used was qualitative. The results showed that students' involvement in the production of Nuris crackers succeeded in improving their understanding of entrepreneurship, especially in the aspects of production management, resource management, and marketing strategies. Thus, the production of Nuris crackers is an effective medium in strengthening students' entrepreneurial skills, as well as contributing to the economy of the local community.